Pengaruh Persepsi Konsumen dan Varian Produk Terhadap Keputusan Pembelian pada Toko Sembako UD. Yani di Kota Bima - Ayu Andriani; Ismunandar Ismunandar; Ovriyadin Ovriyadin (Indo Publishing, 2026)
This study aims to determine the influence of consumer perception and product variety on purchasing decisions at UD. Yani Grocery Store in Bima City. The research employed a quantitative approach with an associative research design. The population consisted of all consumers who had made purchases at UD. Yani Grocery Store, while the sample comprised 96 respondents selected using a purposive sampling technique. Data were collected through observation, interviews, questionnaires, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, partial tests (t-test), and simultaneous tests (F-test) with the assistance of SPSS software. The results showed that consumer perception has a positive and significant effect on purchasing decisions, as indicated by a t-value of 4.049 with a significance value of 0.000. Product variety also has a positive and significant effect on purchasing decisions, with a t-value of 4.711 and a significance value of 0.000. Simultaneously, consumer perception and product variety have a positive and significant effect on purchasing decisions, as evidenced by an F-value of 49.844 and a significance value of 0.000. The coefficient of determination (R²) was 0.517, indicating that 51.7% of purchasing decisions are influenced by consumer perception and product variety, while the remaining 48.3% are explained by other factors not examined in this study. Based on these findings, it can be concluded that better consumer perceptions and a wider variety of products contribute to higher purchasing decisions among consumers at UD. Yani Grocery Store in Bima City.